2019
DOI: 10.1111/boer.12220
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and growth: What comes from the different inequality measures?

Abstract: We would like to thank Aart Kraay for sharing us the replication codes for testing the instrument strength in the inequality-growth regressions with the system GMM estimator, and two anonymous reviewers for helpful comments on early version of our paper. AbstractThe objective of the paper is to verify if income inequality impedes the growth rates in OECD countries in the period of 1990-2014 and to reveal whether the choice of the income inequality measure determines the sign and the strength of the estimated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…While in some of these studies, either a negative or positive relationship was found between higher income inequality and economic growth, in others, the relationship between income inequality and economic growth was found to depend on the country's initial level of income. Studies that found higher income inequality to be associated with lower economic growth include those conducted by Alesina and Rodrik (1994), Persson and Tabellini (1994), Atems and Jones, 2015), Bartak and Jabłoński (2019), among others. Alesina and Rodrik (1994), while examining the relationship between politics and economic growth using a simple endogenous growth model, found that inequality in land and income ownership is negatively correlated with subsequent economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While in some of these studies, either a negative or positive relationship was found between higher income inequality and economic growth, in others, the relationship between income inequality and economic growth was found to depend on the country's initial level of income. Studies that found higher income inequality to be associated with lower economic growth include those conducted by Alesina and Rodrik (1994), Persson and Tabellini (1994), Atems and Jones, 2015), Bartak and Jabłoński (2019), among others. Alesina and Rodrik (1994), while examining the relationship between politics and economic growth using a simple endogenous growth model, found that inequality in land and income ownership is negatively correlated with subsequent economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also found that the relationship between inequality and per capita income varies over time. More recently, Bartak and Jabłoński (2019), while using data from OECD countries during the period 1990-2014 to examine whether income inequality impedes the growth rates, found that income inequality affects economic growth negatively.…”
Section: Literature Reviewmentioning
confidence: 99%